High frequency arbitrary waveform generator using a nonlinear transmission line. Issue 3 (2nd December 2019) - Kim, Chanwoo; Bae, Jaemin; Han, Heeje; Park, Soonwoo; Kim, Hongjoon
Abstract: In this article, a high‐frequency arbitrary waveform generator (AWG) based on Fourier synthesis theory is presented. A key element consists of a nonlinear transmission line (NLTL) that acts as a harmonic generator for large signals and as a phase shifter for small signals. The harmonics generated by the NLTL are separated into four channels using power dividers and each harmonic is bandpass filtered in each channel. The phase and the amplitude are then modulated in each channel by an NLTL phase shifter and a voltage variable attenuator. Finally, vector modulated signals from each channel are combined in Wilkinson power combiners to form any waveform shape. We used 0.5 GHz as a master signal and synthesized waveforms using all four channels.